The mediating role of entrepreneurship in the link between high-speed rail and carbon emissions reduction - Chen, Yu; Chen, Wenqing; Chen, Shan (Frontiers in Environmental Science, 2022)
Prior studies document that the development of transportation infrastructure, particularly the rapid development of high-speed rail, plays a key role in transforming an economy towards a low-carbon development mode, for example by reducing carbon emissions in China and other countries. However, to date, the mechanisms and paths that link high-speed rail to carbon emission reduction remain ambiguous. The present study seeks to clarify this path by proposing the mediating role of entrepreneurship, arguing that the rapid cycle of people, capital, knowledge, and technology induced by high-speed rail would be integrated by entrepreneurs as new start-ups, leading to industry agglomeration, upgrading, and innovations. These consequences of entrepreneurship would further result in carbon emission reductions. Employing a unique dataset in China, we provide strong evidence for our arguments by setting China’s prefecture-level cities as the unit of analysis. The research conclusions are as follows: First, the launch of high-speed rail services has a positive effect on a city’s carbon emission reduction. Second, entrepreneurship plays a mediating role in the relationship between high-speed rail and carbon emission reduction. Third, the administrative approval system reform would strengthen the effect of high-speed rail on entrepreneurship. This study therefore clarifies the path through which high-speed rail leads to carbon emission reduction, and reconfirms the role of transportation development in achieving the goal of sustainable development towards carbon neutrality.